The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.30945/rcr-v20i2.259
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade Fisiológica De Sementes De Feijão Em Função Da Dessecação Química Das Plantas

Abstract: O trabalho procurou avaliar o efeito da aplicação de dois dessecantes, em diferentes épocas, sobre plantas de feijão e seu efeito na qualidade fisiológica das sementes produzidas. A cultivar utilizada foi o carioca TAA Bola Cheia. Os produtos utilizados como dessecantes foram Glufosinato de Amônio, sendo as aplicações realizadas com 30, 50, 70, 90% e Diquate com 50, 70, 90 e 100% das vagens apresentando sementes com a coloração característica da cultivar. As sementes foram colhidas quando atingiram 16% de umid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
(5 reference statements)
0
3
0
1
Order By: Relevance
“…Desiccation of soybean seeds using ammonium glufosinate, paraquat, and carfentrazone applied at the R7.1 stage showed no reduction in germination (Pereira et al, 2015). Lima et al (2018) used ammonium glufosinate and diquat to desiccate cowpea plants found no differences in germination and vigor right after harvest when desiccation was carried out between 50 and 100% of brown-colored pods.…”
Section: Resultsmentioning
confidence: 91%
“…Desiccation of soybean seeds using ammonium glufosinate, paraquat, and carfentrazone applied at the R7.1 stage showed no reduction in germination (Pereira et al, 2015). Lima et al (2018) used ammonium glufosinate and diquat to desiccate cowpea plants found no differences in germination and vigor right after harvest when desiccation was carried out between 50 and 100% of brown-colored pods.…”
Section: Resultsmentioning
confidence: 91%
“…Seeds coming from the treatment with glufosinate ammonium had a percentage of normal seedlings after accelerated aging lower than the percentages from the other treatments. According to Lima et al (2018), seeds from common bean desiccated with glufosinate ammonium at different time periods have lower NSAA values in relation to the untreated control. Tavares et al (2016) also observed effects after storage of seeds coming from a treatment with application of paraquat for desiccation of azuki bean.…”
Section: Resultsmentioning
confidence: 99%
“…High quality seeds depend on harvest occurring at the ideal time, frequently when physiological maturity is reached, coinciding with maximum accumulation of seed dry matter, high vigor, and high germination (Lima et al, 2018). One of the alternatives is desiccant herbicide prior to harvest, which can reduce exposure of seeds to unfavorable environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Se han desarrollado varios estudios que abordan el tema del uso de herbicidas como desecantes para diversos cultivos, como soja (Glycine max) (Marchi et al, 2021), frijol común (Phaseolus vulgaris) (Lima et al, 2018), sorgo (Sorghum bicolor) (Barros et al, 2019) y trigo (Triticum) (Souza et al, 2020). Sin embargo, para el cultivo de frijol existen pocos trabajos que puedan orientar a los agricultores en la elección del desecante adecuado, especialmente en la región norte de Brasil.…”
Section: Volumen 35 (2023) Bioagro N°1unclassified